2017
DOI: 10.1017/s0021859617000417
|View full text |Cite
|
Sign up to set email alerts
|

A fungal endophyte consortium counterbalances the negative effects of reduced nitrogen input on the yield of field-grown spring barley

Abstract: SUMMARYThe use of chemicals to fertilize crops incurs economic and environmental costs and it is widely recognized that the current level of chemical fertilizer use is unsustainable in many intensive farming systems. Any methods that can reduce fertilizer input and still maintain acceptable yields would be of great benefit to both the farmer and the environment. The use of beneficial endophytes as crop inoculants may go some way towards improving crop yields beyond that achievable using fertilizer increases al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A mixture of endophytic fungi isolated from wild barley eff ectively suppressed the seed-borne infections in a barley cultivar (Murphy et al, 2015). A fungal endophyte consortium consistently improved barley grain yield over several seasons under a variety of chemical fertilizer inputs and low seasonal rainfall (Murphy et al, 2017). Intra-or interspecies fungal consortia consisting of Clonostachys, Beauveria, Metarhizium or Trichoderma spp.…”
Section: Fungal Mixturesmentioning
confidence: 99%
“…A mixture of endophytic fungi isolated from wild barley eff ectively suppressed the seed-borne infections in a barley cultivar (Murphy et al, 2015). A fungal endophyte consortium consistently improved barley grain yield over several seasons under a variety of chemical fertilizer inputs and low seasonal rainfall (Murphy et al, 2017). Intra-or interspecies fungal consortia consisting of Clonostachys, Beauveria, Metarhizium or Trichoderma spp.…”
Section: Fungal Mixturesmentioning
confidence: 99%
“…There are numerous reports describing the benefits of fungal endophytes on seed germination, seedling vigor, abiotic, and biotic stress tolerance, and increased biomass of crop plants [ 38 , 40 , 41 , 42 , 43 , 44 , 45 ]. Although there are comparatively few reports on endophytes improving crop production under field conditions [ 38 ], fungal endophytes have shown good field efficacy for enhancing yields, biological control, and improving yield quality [ 38 , 43 , 44 , 45 ]. Extensive field testing demonstrated that ThSM3a conferred tolerance to drought and temperature extremes in both a monocot (corn) and eudicot (cotton).…”
Section: Discussionmentioning
confidence: 99%
“…The approach we have adopted in developing a crop inoculant, as outlined in this paper, has resulted in the successful translation of promising laboratory-based research to agriculture. In field trials with barley, we found that for an endophyte-associated increase in grain yield, a strong correlation was found between increased yield and low seasonal rainfall [ 31 ]. Furthermore, the endophytes were just as effective with regular foliar fungicidal treatment.…”
Section: Translationmentioning
confidence: 99%
“…The approach adopted by our research group has consciously focused on making this transition from ‘pot to plot’ more successful. We aimed to remove the inconsistency from endophyte application in field crops by targeting a single crop, barley, as our model plant, and testing the efficacy of endophyte strains under various environmental stresses, culminating in extensive field trials [ 30 , 31 , 32 , 33 , 34 , 35 ]. Only with this field validation can we say with any confidence that a microbial inoculant really “works” [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation